Faktor Faktor yang Mempengaruhi Perilaku Membuang Makanan (Food Waste) Rumah Tangga di Daerah Perbatasan Kabupaten Sanggau - Muhamad Kardiansyah; Maswadi Maswadi; Wanti Fitrianti (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Food waste is becoming an increasingly significant global issue along with food loss and waste, consumers throw away 31% of the food they have purchased, a third of the total food produced globally or around 1.3 billion tons of food that can be consumed including fresh vegetables, fruit. , meat, bread and dairy products are lost along the supply chain. Food waste has many negative social, economic and environmental impacts. The household sector is one area that contributes to a significant amount of food waste. Household behavior is considered the biggest contributor to food waste. wasted (Food Waste), behavior shows significant differences in producing food waste produced by households, Sanggau Regency also experiences problems with food waste, this cannot be separated from the geographical conditions of the area which borders directly with the Malaysian region which makes the mobility of goods difficult. easier, thus making the community's consumptive factor increase as evidenced by the continued increase in public demand for food products produced by the people of Sanggau Regency every year. This research aims to identify household consumption behavior regarding the behavior of throwing away food (food waste) in border areas of the Regency. Sanggau and determine the influence of socio-demographic, socio-economic factors and household consumption behavior on food waste behavior in the border areas of Sanggau Regency. The research method used in this research is descriptive statistics. The sample in this study was 100 respondents representing households. The variables in this research are divided into two, namely respondent characteristics and household behavior. The results of the research show that the average food waste behavior in households refers to the characteristics of respondents such as age, gender, occupation, income, expenditure and number of family members as well as tendencies or behavioral patterns of household members in producing, managing and using food. causes food to be wasted in an inefficient manner. Food waste behavior covers various aspects, including purchasing, storing, preparing and consuming food.